Prevalence of Gastro Intestinal Parasites in Working Equids of Tamil Nadu, India - P.Athilakshmy; C.Manivannan; K.T. Kavitha; P.Kumaravel; N.Vimal Rajkumar; N.Kumaravelu; G.Kathiravan (The Indian Veterinary Journal, 2024)
The study was conducted from April 2023 to September 2023 in twelve locations of Tamil Nadu to find out the prevalence of gastro intestinal parasites and assess the associated risk factors in working equids. A total of 179 faecal samples were collected randomly from equines (40 Horses, 63 Ponies and 76 Donkeys) and examined using standard coprological techniques. The overall prevalence rate of gastrointestinal parasites was found to be 41.34 per cent with an incidence rate of 44.44 per cent, 40.00 per cent and 39.47 per cent in ponies, horses and donkeys respectively. The prevalence of strongyle infection was found to be highest (28.49%) followed by mixed infection of Strongyle species with Parascaris equorum (5.59 %) and others. Among the risk factors assessed, the parameter viz. body condition score (BCS) was strongly associated (p<0.0001), while the factors such as housing condition (p=0.0391) and terrain (p=0.020) had a significant association with prevalence rate.